Co-Treatment With Verapamil and Curcumin Attenuates the Behavioral Alterations Observed in Williams–Beuren Syndrome Mice by Regulation of MAPK Pathway and Microglia Overexpression - Ortiz-Romero, Paula; González-Simón, Alejandro; Egea, Gustavo; Pérez-Jurado, Luis A.; Campuzano, Victoria (Frontiers in Pharmacology, 2021)
Williams-Beuren syndrome (WBS) is a rare neurodevelopmental disorder characterized by a distinctive cognitive phenotype for which there are currently no effective treatments. We investigated the progression of behavioral deficits present in WBS complete deletion mice (CD), after chronic treatment with curcumin, verapamil and a combination of both. These compounds have been proven to have beneficial effects over different cognitive aspects of various murine models and thus, may have neuroprotective effects in WBS. Treatment was administered orally dissolved in drinking water. A set of behavioral tests demonstrated the efficiency of combinatorial treatment. Some histological and molecular analyses were performed to analyze the effects of treatment and its underlying mechanism. CD mice showed an increased density of activated microglia in the motor cortex and CA1 hippocampal region, which was prevented by cotreatment. Behavioral improvement correlated with the molecular recovery of several affected pathways regarding MAPK signaling, in tight relation with the control of synaptic transmission, and inflammation. Therefore, results show that cotreatment prevented behavioral deficits by recovering altered gene expression in cortex of CD mice and reducing activated microglia. These findings unravel the mechanisms underlying the beneficial effects of this novel treatment on behavioral deficits observed in CD mice, and suggest that the combination of curcumin and verapamil could be a potential candidate to treat the cognitive impairments in WBS patients.